ENZYMATIC, CHEMOENZYMATIC and PHOTOENZYMATIC CASCADE REACTIONS: PERSPECTIVES FOR A MORE SUSTAINABLE ORGANIC SYNTHESIS - Castilho, Shirley A. [UNESP]; Milagre, Humberto M.S. [UNESP]; Milagre, Cintia D.F. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2022)
Chemicals are rarely the result of a single transformation but rather the consequence of several individual reaction steps. Classically, these individual steps are carried out in sequence, including isolation and purification of the intermediate products. However, the reasons for choosing to carry out cascade reactions can be multiple, such as (i) the chance to prepare unstable and/or toxic intermediates, which are consumed directly in a subsequent step, (ii) the option to shift the equilibrium of a reaction by removing the co (product), or (iii) simply bypass the tedious work of isolating and purifying intermediates, saving reagents, solvents, time and money, and still generating less waste. Therefore, it is not surprising that so-called cascade reactions are gaining considerable interest in academic and industrial research. The purpose of this review is to show recent, promising research and new trends, the potential and current limitations of cascade reactions in organic synthesis that involves at least one enzymatic step in the cascade. This review will address cascades involving multi enzymatic, chemoenzymatic, and photoenzymatic cascades, where all steps are performed in one reaction vessel simultaneously or sequentially and the cascades in the regime of continuous flow.
REAÇÕES EM CASCATA ENZIMÁTICA, QUIMIOENZIMÁTICA E FOTOENZIMÁTICA: PERSPECTIVAS PARA UMA SÍNTESE ORGÂNICA MAIS SUSTENTÁVEL
Keywords: biocatalysis; cascade reaction; green chemistry; organic synthesis; sustainable chemistry